ERKIN VAHIDOV'S POETIC INTERPRETATION OF THE THEME OF HISTORY IN THE UZBEGIM ODE - Baltayeva Z.Sh. (Web of Journals Publishing, 2024)
The article analyzes the poetic development of the theme of history in folk poems by the national poet of Uzbekistan Erkin Vahidov, how he gives the poem a little charm and introduces the reader to our national history, the nature of the lyrical image, the uniqueness of spiritual experience and the expressive style in Work of the poet. It theoretically summarizes the author's ability to form a lyrical character, the expression of the realism of the historical spirit, the degree of uniqueness of the pictorial aesthetic choice and the scope of the subject of the pictorial conception of the worldview.
Keywords: realism of the historical spirit, independence of expression, nature of the creator, coverage of the image, lyrical character development, literary interpretation, artistic style, depth of analysis, philosophical observation.